Consejos para pleanear contra desastres para gente mayor - Carolyn S. Wilken; Linda B. Bobroff; Emily Minton (EDIS)
FY1462 is the Spanish-language version of FCS9198/FY620: Disaster Planning Tips for Older Adults. This 4-page publication offers an abundance of information pertaining to water storage and use, food, first aid, important papers, electronics, medical needs, stress reduction, and evacuation which can help older adults plan for natural disasters and other emergencies. Written by Carolyn Wilken, Linda B. Bobroff, and Emily Minton, and published by the Department of Family, Youth and Community Sciences, May 2003. Revised September 2015.